Resistência à brusone de genótipos de trigo com ampla variabilidade genética e capacidade esporulativa de Pyricularia oryzae - Kovaleski, Marcos (2020)
Blast, which its causal agent is the fungus Pyricularia oryzae, is a plant disease that causes great damage to wheat fields in Brazil. Besides being favored by the unavailability of wheat cultivars with appropriate resistance to this disease, the large production of conidia generated by its causal agent intensifies the occurrence of blast in the Brazilian wheat fields. The prospection of new sources of resistance to blast on wheat germplasm different from the one currently used in Brazil is an important action in order to obtain resistance to this disease. In this sense, the objectives of the present study were to: a) characterize wheat genotypes with wide genetic variability according their resistance to blast; b) verify the effect that temperature has on the sporulation of P. oryzae on segments of wheat plants and; c) evaluate the sporulative capacity of P. oryzae on wheat leaf lesions. The experiments were carried out under controlled conditions at the Embrapa Trigo, Passo Fundo, RS. A collection of wheat genotypes, including Mexican lineages, was evaluated for the reaction of blast on spikes and spike rachis. In the spikes, the severity of the disease was evaluated in two moments post-inoculation. In the spike rachis, the severity of the disease, the number of infection points, and spore production were evaluated. Genotypes with the 2NS/AS translocation showed greater resistance to blast compared to those that did not have it. The progenitor Milan's genealogical descent did not result in a higher level of resistance. Important information about the sporulative capacity of P. oryzae were also obtained. It was verified that the reproductive capacity of P. oryzae on lesions of leaves, stems and wheat rachis was dependent on the temperature. The greatest amount of conidia/g of tissue was observed at 27 °C. Under the lowest and highest temperatures tested, 18 and 33 °C, respectively, the sporulation of P. oryzae decreased considerably. Pyricularia oryzae isolates produced quantities of conidia ranging from 0.67 x105 to 1.27x105 conidia/mm² of injured leaf area. There was a great difference among the tested genotypes in relation to the variables evaluated but a group of them stood out in terms of blast resistance. Information obtained in this study auxiliary to dimension the role that wheat plants themselves represent to wheat blast development as source of inoculum for the disease.